Pengaruh Kenaikan Harga Gadget terhadap Keputusan Pembelian Konsumen di Era Digital - Muhammad Taruna Sakti Batubara; Ika Khairi Dzaky Nasution; Shella Anjelika Br Tampubolon; Delila Lumban Raja; Sakila Putri; Winadya Norma Septelina Simare Mare; Radhitya Dava Gurusinga; Nurul Wardani Lubis (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The continuous increase in gadget prices has become an important issue in the digital era because these devices are no longer considered luxury products but essential tools for education, work, communication, and daily activities. Rising production costs, technological innovation, exchange rate fluctuations, and global economic conditions have contributed to higher market prices, potentially influencing consumer purchasing decisions. This study aims to examine the effect of increasing gadget prices on consumer purchasing decisions. A quantitative survey was conducted using purposive sampling involving 60 respondents who had purchased or used gadgets. Data were collected through an online questionnaire and analyzed using validity and reliability tests, descriptive statistics, and simple linear regression. The findings reveal that consumers are increasingly selective when purchasing gadgets. Many respondents prefer delaying purchases, waiting for promotional offers, or considering more affordable alternatives. Nevertheless, gadgets remain essential products, encouraging consumers to continue purchasing them despite higher prices. Statistical analysis indicates that rising gadget prices have a positive and significant effect on purchasing decisions and explain a moderate proportion of consumer decision variability. These findings suggest that consumers evaluate not only price but also product usefulness, quality, features, and overall value before making purchasing decisions.